Growth performance and efficiency of protein utilization in giant tiger prawn, Penaeus monodon reared in tarpaulin pond with and without faecal chamber - Saade, Edison; Fachruddin, Liestiaty; Anshary, Hilal; Lante, Samuel; Haryati, Haryati; Said, Rosmala D.; Wanda, Amalia; Arlini, Fitriwi (Gorontalo State University, 2021)
The accumulation of organic matter at the bottom of the pond greatly affects nutrient metabolism, feed efficiency, growth and productivity in giant tiger prawn cultivation. One of the causes is improper pool bottom construction The purpose of this study was to compare the growth performance and efficiency of protein utilization in giant tiger prawns consuming artificial feed supplemented with multi-enzymes and reared in tarpaulin ponds constructed between not and using the faecal chamber (FAMBER) or the space of metabolic waste and unconsumptioned feed (SOMECOF) at the bottom of the pond with a recirculating aquaculture system (RAS). A tarpaulin pond with a diameter of 3 m and a height of 100 cm filled with 80 cm of seawater. The tarpaulin pond is equipped with a transparent plastic roof, seawater and aeration installation, and a filter in the water pump tank. The average body weight of the experimental prawn used were 8-9 g. The feed given is pellet type artificial feed supplemented with multi-enzymes at a dose of 30 cc/kg of feed. The frequency of feeding were four times a day, namely at 07:00; 12:00; 17:00 and 22:00 with a dose of 5%. The parameters measured were growth performance including growth, condition factors and feed efficiency, while the efficiency of protein utilization included protein content, protein efficiency ratio, amino acid profile, index and score of essential amino acids of feed and experimental prawn. Data analysis was done descriptively. The results showed that all parameters of growth performance and efficiency of protein utilization in tiger prawns reared in tarpaulin ponds using FAMBER were better than those without FAMBER. Based on the results of the study, it was concluded that keeping giant tiger prawns in a tarpaulin pond using a FAMBER is better than not using a FAMBER.